ANALISIS PSIKOLOGI SASTRA NOVEL KATARSIS KARYA ANASTASIA AEMILIA - Dewi Wulan Sari, Anak Agung (Humanis; Volume 10. No 3. Maret 2015)
This study aims to analyze and understand the personality of a character in the novel aspects of Catharsis. Novel Catharsis is used as an object of research. The object of research was analyzed using structural theory, psychology and literary theory. In the case analyzed in terms of the structural elements of the story builders, ie plot, character, and background. In terms of the psychology literature analyzed in terms of the characteristics of antisocial personality disorder
Keywords: structural theory, theories of psychology literature, antisocial personality disorder